Hydrothermal Liquefaction of Food Waste: Effect of Process Parameters on Product Yields and Chemistry - Bayat, Hengameh; Dehghanizadeh, Mostafa; Jarvis, Jacqueline M.; Brewer, Catherine E.; Jena, Umakanta (Frontiers in Sustainable Food Systems, 2021)
Increasing food waste generation (1.6 billion tons per year globally) due to urban and industrial development has prompted researchers to pursue alternative waste management methods. Energy valorization of food waste is a method that can reduce the environmental impacts of landfills and the global reliance on crude oil for liquid fuels. In this study, food waste was converted to bio-crude oil via hydrothermal liquefaction (HTL) in a batch reactor at moderate temperatures (240–295°C), reaction times (0–60 min), and 15 wt.% solids loading. The maximum HTL bio-crude oil yield (27.5 wt.%), and energy recovery (49%) were obtained at 240°C and 30 min, while the highest bio-crude oil energy content (40.2 MJ/kg) was observed at 295°C. The properties of the bio-crude oil were determined using thermogravimetric analysis, fatty acid methyl ester (FAME) analysis by gas chromatography with flame ionization detection, CHNS elemental analysis, and ultrahigh-resolution Fourier transform ion cyclotron resonance mass spectroscopy (FT-ICR MS). FT-ICR MS results indicated that the majority of the detected compounds in the bio-crude oil were oxygen-containing species. The O4 class was the most abundant class of heteroatom-containing compounds in all HTL bio-crude oil samples produced at 240°C; the O2 class was the most abundant class obtained at 265 and 295°C. The total FAME content of the bio-crude oil was 15–37 wt.%, of which the most abundant were palmitic acid (C16:0), palmitoleic acid (C16:1), stearic acid (C18:0), and polyunsaturated fatty acids (C18:3N:3, C18:3N:6).